2017
DOI: 10.1123/apaq.2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Influences on Development of Athletes With Disabilities

Abstract: Compared with mainstream sport athletes, relatively little is known regarding the factors affecting the development of athletes with a disability. Sport-specific training programs are essential to athletes' successful performance; to create appropriate programs and strategies, a clear understanding of the nuances of development of athletes with a disability is important. The objective of this systematic review was to synthesize existing research on development in athletes with a disability and examine the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 14 publications
3
24
0
1
Order By: Relevance
“…It allows to increase motor activity level to restore muscular strength and joints mobility, to expand the arsenal of motor skills. The results of our research are confirmed by certain number of scientific works, that are devoted to the rehabilitation orientation of adaptive sports as a means of strengthening health, restoring lost functions, adapting to external conditions, physical development and preparedness improvement (DePauw & Gavron, 1995;Houwen, Visscher, Hartman & Lemmink, 2007;Blauwet & Willick, 2012;Lastuka & Cottingham, 2015;Dehghansai, Lemez, Wattie & Baker, 2017).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It allows to increase motor activity level to restore muscular strength and joints mobility, to expand the arsenal of motor skills. The results of our research are confirmed by certain number of scientific works, that are devoted to the rehabilitation orientation of adaptive sports as a means of strengthening health, restoring lost functions, adapting to external conditions, physical development and preparedness improvement (DePauw & Gavron, 1995;Houwen, Visscher, Hartman & Lemmink, 2007;Blauwet & Willick, 2012;Lastuka & Cottingham, 2015;Dehghansai, Lemez, Wattie & Baker, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…In modern society, the search for solutions for problem solving of persons' with disabilities social integration is considered within framework of the new special means of substantiation, methods and technologies of persons' with disabilities adaptation to the external environment (Blauwet & Willick, 2012;Herasymenko, Mukhin, Pityn & Kozibroda, 2016;Rudenko, Hlozhyk, Guzii & Prystupa, 2017). At the same time, one of the most effective socialization means for persons with disabilities has been actively developing -adaptive sports (Dehghansai, Lemez, Wattie & Baker, 2017). It's as unique social phenomena that has no analogues in modern society allows to create conditions for the attraction persons with disabilities to social life by providing the opportunity to realize their own potential in activities that have a social significance (Sahlin & Lexell, 2015;Lastuka & Cottingham, 2015;Jaarsma, Dekker, Geertzen & Dijkstra, 2016;Fagher, Jacobsson, Timpka, Dahlström & Lexell, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It allows to increase motor activity level to restore muscular strength and joints mobility, to expand the arsenal of motor skills. The results of our research are confirmed by certain number of scientific works, that are devoted to the rehabilitation orientation of adaptive sports as a means of strengthening health, restoring lost functions, adapting to external conditions, physical development and preparedness improvement (DePauw & Gavron, 1995;Houwen, Visscher, Hartman & Lemmink, 2007;Blauwet & Willick, 2012;Lastuka & Cottingham, 2015;Dehghansai, Lemez, Wattie & Baker, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…In modern society, the search for solutions for problem solving of persons' with disabilities social integration is considered within framework of the new special means of substantiation, methods and technologies of persons' with disabilities adaptation to the external environment (Blauwet & Willick, 2012;Herasymenko, Mukhin, Pityn & Kozibroda, 2016;Rudenko, Hlozhyk, Guzii & Prystupa, 2017). At the same time, one of the most effective socialization means for persons with disabilities has been actively developing -adaptive sports (Dehghansai, Lemez, Wattie & Baker, 2017). It's as unique social phenomena that has no analogues in modern society allows to create conditions for the attraction persons with disabilities to social life by providing the opportunity to realize their own potential in activities that have a social significance (Sahlin & Lexell, 2015;Lastuka & Cottingham, 2015;Jaarsma, Dekker, Geertzen & Dijkstra, 2016;Fagher, Jacobsson, Timpka, Dahlström & Lexell, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Paralympics has grown from a small gathering of British World War II veterans in 1948 to become one of the largest international sporting events in the early 21st century. The Paralympics has grown from 400 athletes with disabilities from 23 countries in 1960 to thousands of competitors from over 100 countries in the London 2012 Games ( Dehghansai et al, 2017 ). The etymology of ‘paralympics’ reveals that it was meant to be held in parallel with the Olympics, as the prefix, ‘para’ means side by side.…”
mentioning
confidence: 99%